Debt Management and Economic Development: Evidence from Nigeria - Ofurum, Clifford Obiyo; Egbe, Solomon; Sawyer, Morris Ebikeniye (Archives of Business Research, 2022)
The study examined Nigeria’s public debt management and economic development. Specifically, the study aims to establish a nexus between domestic debt management and two dimensions of economic development, the human development index and foreign currency reserve. The study adopted positivism as a philosophical basis and used time series data from 1981 to 2021. This study employs the Autoregressive Distributive Lag (ARDL) model, and E-view were used for analyses. The result did not reveal a meaningful relationship between domestic debt management and economic development. The study concludes that the large variability in economic development observed in Nigeria can only be related to the combined effects of the public debt management variables and not their individual effects. The study recommends that the government ensure that it operates a productive rather than a consumer economy, moderate external borrowing, and create an environment conducive to foreign investment.